301 Long term sequelae after COVID-19: the different impact on the right and left ventricles. (8th December 2021) - Pelà, Giovanna; Aiello, Marina; Goldoni, Matteo; Cavalli, Chiara; Perrino, Felice; Mantovanelli, Luca; Frizzelli, Annalisa; Letizia, Davide Maria; Tagliaferri, Sara; Pizzi, Valentina; Mori, Pier Anselmo; Majori, Maria; et al.
Abstract: Aims: Most patients who had COVID-19 are still symptomatic after many months post infection, but the long-term outcomes are not yet well-defined. The aim of our prospective/retrospective study was to define the cardiac sequelae of COVID-19 infection. Methods and results: This monocentric cohort study included 160 consecutive patients (64 females, 60 + 12 years) who had been discharged from the ward or from the outpatient clinic after a diagnosis of COVID-19 and subsequently referred for a follow-up visit. Clinical features as well as lab and instrumental data about the acute phase of the disease, such as haemodynamic instability (HI), cardiac biomarkers, d -dimer, C-reactive protein (CRP), high resolution CT (HRCT) score along with information about the follow-up visit, including ECG and Conventional and Doppler Tissue Echocardiographic (DTE) parameters, were recorded. The median follow-up time after symptom onset was 5 months. At follow-up visit, the majority of the patients reported dyspnoea and asthenia. Moreover, echocardiography showed morpho-functional changes of both right (RV) and left (LV) ventricles, such as RV dilation, increased pressure in the pulmonary circulation, and by-ventricular systolic–diastolic dysfunction. When examined using multivariate analysis, independent of age, sex, and co-morbidities, RV and LV changes were significantly associated ( P < 0.05) with HRCT score and HI and with CRP, respectively. Conclusions: Our results suggest that COVID-19 may impact RV and LV differently. Notably, the extent of the pneumonia and HI may affect RV, whereas the inflammatory status may influence LV. A long-term follow-up is warranted to refine and customize the most appropriate therapeutic strategies.